Alien reptiles on Mediterranean Islands: A model for invasion biogeography. Issue 6 (13th March 2019) - Silva‐Rocha, Iolanda Raquel; Salvi, Daniele; Carretero, Miguel A.; Ficetola, Gentile Francesco
Abstract: Aim: The Mediterranean basin has a long history of interactions between humans and biota, with multiple ancient and recent introductions of alien species. Such a multitude of introductions makes it difficult to distinguish between alien and native species but provides an excellent opportunity to investigate factors related to introductions and long‐term persistence of alien species. In this study, we combined genetic and distribution data to identify the factors promoting the presence of alien reptiles on islands, considering human‐related, geographic and species features. Furthermore, we assessed whether the use of genetic evidence to identify alien species improves inference of the factors determining their distribution. Location: Mediterranean islands. Methods: We combined genetic data and distribution databases to obtain information on biological traits and on the native/alien status of reptiles on >900 Mediterranean islands, and we gathered data on geographic and human features of islands. We then used spatially explicit generalized additive mixed models to identify the factors associated with the establishment of alien reptiles. Results: Alien reptile populations are more frequent on islands far from the native range and with large human population. Alien populations of reptiles that are able to feed on plants are particularly frequent. Traditional data sources underestimate the frequency of alien reptiles on Mediterranean islands, and using genetic evidence to assess the status of populations provided a more complete picture of the factors associated with the presence of alien populations. Main conclusions: Humans are key drivers of the distribution of alien reptiles on Mediterranean islands, but the distributions are determined by a complex interplay between human activities, geographic factors and species features. Genetic data are essential for obtaining reliable biogeographic assessments of invasive species, particularly in systems with a long history of human influence.